Preparation of polyamide 6/silica nanocomposites from silica surface initiated ring-opening anionic polymerization (eXPRESS Polymer Letters, 2007)
Polyamide 6/silica nanocomposites were synthesized by in situ ring-opening anionic polymerization of ε-caprolactam in the presence of sodium caprolactamate as a catalyst and caprolactam-functionalized silica as an initiator. The initiator precursor, isocyanate-functionalized silica, was prepared by directly reacting commercial silica with excess toluene 2,4-diisocyanate. This polymerization was found to occur in a highly efficient manner at relatively low reaction temperature (170°C) and short reaction times (6 h). FTIR spectroscopy was utilized to follow the introduction and consumption of isocyanate groups on the silica surface. Thermogravimetric analysis indicated that the polyamide 6 was successfully grown from the silica surface. Transmission electron microscopy was utilized to image polymer-functionalized silica, showing fine dispersion of silica particles and their size ranging from 20 to 40 nm.